2006
DOI: 10.1243/09576509jpe171
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the flowfield through a variable geometry turbine stator with vane endwall clearance

Abstract: Variable geometry turbines provide an extra degree of flexibility in air management in turbocharged engines. The pivoting stator vanes used to achieve the variable turbine geometry necessitate the inclusion of stator vane endwall clearances. The consequent leakage flow through the endwall clearances impacts the flow in the stator vane passages and an understanding of the impact of the leakage flow on stator loss is required. A numerical model of a typical variable geometry turbine was developed using the comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A hub endwall clearance of 0.215mm was introduced and an H/J/C/L grid type in conjunction with an O-Grid of width factor 0.2 was used as it was found to yield the best results in terms of mesh skewness. The number of elements was set to 280,000, and the tip clearance was modelled with 10 equispaced node points, which are similar values to those employed by Spence et al, 2006 [9]. Furthermore, as the SST turbulence model was employed, a y + value close to unity was required in order to resolve the details in the boundary layer.…”
Section: Computational Methodologymentioning
confidence: 99%
“…A hub endwall clearance of 0.215mm was introduced and an H/J/C/L grid type in conjunction with an O-Grid of width factor 0.2 was used as it was found to yield the best results in terms of mesh skewness. The number of elements was set to 280,000, and the tip clearance was modelled with 10 equispaced node points, which are similar values to those employed by Spence et al, 2006 [9]. Furthermore, as the SST turbulence model was employed, a y + value close to unity was required in order to resolve the details in the boundary layer.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Several early studies have shown that at small nozzle openings, turbine stage performance is seriously affected by nozzle endwall leakage flow. 914 In case the length of the nozzle endwall clearance can be reduced effectively, there will be a great mitigation in nozzle leakage flow rate. Based on this idea, the FRGV design is carried out.…”
Section: Research Modelmentioning
confidence: 99%
“…Some studies highlighted the characteristics of nozzle leakage flow by CFD methods. Research works of Spence et al 11 and Walkingshaw et al 12 indicated that the nozzle leakage flow interacted with the main flow to produce continuous dissipating leakage vortex, which then causes flow losses. Besides that, the characteristics of leakage vortex also varied considerably with guide vane position.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows the three vane angle settings used in the testing and the measured surfaces. The suction and pressure surfaces are indicated similar to the reference [13].…”
Section: Vane Surface Static Pressure Surveymentioning
confidence: 99%